1991
DOI: 10.1515/znc-1991-11-1218
|View full text |Cite
|
Sign up to set email alerts
|

Is the in vivo Photosystem I Function Resistant to Photoinhibition? An Answer from Photoacoustic and Far-Red Absorbance Measurements in Intact Leaves

Abstract: Preillumination o f intact pea leaves with a strong blue-green light o f 400 W m "2 markedly inhibited both photoacoustically monitored 0 2-evolution activity and PS II photochemistry as estimated from chlorophyll fluorescence measurements. The aim o f the present work was to examine, with the help o f the photoacoustic technique, whether this high-light treatment dete riorated the in vivo PS I function too. High-frequency photoacoustic measurements indicated that photochemical conversion o f far-red light ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 9 publications
3
9
0
Order By: Relevance
“…High-light intensity is known to induce photoinhibition, that is, the energy dissipating mechanisms in competition with the radiative relaxation of Chl. The consequent reduction in ChlF was seen to be more marked on F685 than F735 (Agati 1998), in agreement with the greater resistance of PSI-as compared to PSII-to strong light stress (Havaux and Eyletters 1991) and with results from fluorescence measurements at 77 K (Demmig and Bjorkman 1987;Somersalo and Krause 1989). Photoinhibition at chilling temperatures was also observed to affect PSII, but not PSI, activity (Huang et al 2010).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…High-light intensity is known to induce photoinhibition, that is, the energy dissipating mechanisms in competition with the radiative relaxation of Chl. The consequent reduction in ChlF was seen to be more marked on F685 than F735 (Agati 1998), in agreement with the greater resistance of PSI-as compared to PSII-to strong light stress (Havaux and Eyletters 1991) and with results from fluorescence measurements at 77 K (Demmig and Bjorkman 1987;Somersalo and Krause 1989). Photoinhibition at chilling temperatures was also observed to affect PSII, but not PSI, activity (Huang et al 2010).…”
Section: Discussionsupporting
confidence: 79%
“…PSI seems to be much less sensitive to photochemistry (Krause and Weis 1991) and more resistant than PSII to strong light stress (Havaux and Eyletters 1991). Therefore, any change in the above quenching parameters should be reflected in a change in the Chl F685/F735.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, from a qualitative point of view, the closure of the PSI centers during heat stress in the dark could be interpreted as the adjustment of the PSI photochemical efficiency to the decreased rate of photochemistry in PSII. Interestingly, a relationship between Bx and V similar to that observed during heat stress in the dark was measured after a photoinhibitory treatment affecting specifically PSII (Havaux and Eyletters 1991). Overall, it can be concluded that short exposures of intact pea leaves to high temperature affected both PSI and PSII.…”
Section: P68o~ --P68osupporting
confidence: 65%
“…Cyclic electron flow through PSI may act to maintain a strong transthylakoid proton gradient and high thermal de-excitation at PS II under such conditions of severe photoinhibition. PSI is known to be much more resistant to photoinhibition than is PS II (Canaani et al 1989, Havaux and Eyletters 1991). Further, Topf et al (1992 have observed that photoinhibition of PS II in Chlamydomonas causes a stimulation of cyclic electron flow through PSI that in turn functions to maintain the transthylakoid proton gradient in photoinhibited cells.…”
Section: Regulation Of Photosystem Hmentioning
confidence: 99%